Association of age at first sex with HIV-1, HSV-2, and other sexual transmitted infections among women in northern Tanzania. - Ghebremichael, Musie; Larsen, Ulla; Paintsil, Elijah (Sexually transmitted diseases, 2009)
To examine the association between age at first sex and the prevalence of sexually transmitted infections (STIs), including HIV-1 and HSV-2, in women in Moshi urban district, northern Tanzania.
Keywords: Adult; Age Factors; Coitus; Female; Herpes Genitalis; Herpesvirus 2, Human; HIV Infections; HIV-1; Humans; Interviews as Topic; Prevalence; Sexually Transmitted Diseases; Tanzania; Young Adult